SWOT-AHP analysis of the Korean satellite and space industry: Strategy recommendations for development - Lee, Junho; Kim, Ikjun; Kim, Hyomin; Kang, Juyoung (Technological Forecasting and Social Change, 2021)
The global satellite industry is growing in the private market with the advent of SpaceX Corp., Planet Labs Corp., and so forth. Following this trend, the Korean government established the National Space Commission to construct a space development plan that encourages private companies’ participation. Korea has the potential to create various satellite services based on its information technology and semiconductor industries. Thus, this study aims to present strategies to accelerate the growth of the satellite industry by considering various internal and external factors, such as the limitations and strengths of the Korean space and satellite industry. This study employs the SWOT-AHP method, to measure these items factors priorities’ and suggest in-depth strategies. The SWOT matrix is constructed based on prior research. Then, an AHP survey of 32 experts is conducted, and strength-threat and strength-opportunity strategies are developed using the top eight relatively important items. The analysis finds that opportunity items have high priorities. Thus, a strategy is devised to meet demand in the public sector and vitalize private businesses. Lastly, topics are collected using latent Dirichlet allocation topic modeling to identify the media's perspective, which we find is similar to the opinions of the experts chosen for this study.
Keywords: Internal and external factors; Korean Government; Latent Dirichlet allocation; Private companies; Satellite industry; Satellite services; Semiconductor industry; Space development; Satellite; South korean space and satellite industry; Strategy; SWOT-AHP; Topic modeling